Research progress on geogenic-contaminated high ammonium groundwater - Yao DU; Yaojin XIONG; Yamin DENG; Yanxin WANG (Shuiwen dizhi gongcheng dizhi)
Groundwater nitrogen contamination is one of the most prevalent water environment problems worldwide. For a long time, the high concentration of ammonium in groundwater has been attributed to inputs from various human activities. However, the natural ammonium anomalies in groundwater have been neglected in previous studies. This paper reviewed the potential sources of ammonium in groundwater systems from anthropogenic sources including domestic and industrial wastewater discharges, domestic landfills, fertilizer and pesticide applications, sewage irrigation, and geological sources of natural organic matter mineralization. The global distribution of geogenic high-ammonium groundwater was also summarized. From the perspectives of depositional and hydrogeochemical environments, it is summarized that the occurrence characteristics of geogenic ammonium in groundwater systems were organic matter-rich, stagnant, confined, and reducing conditions. Based on two typical case studies, it is clarified that the evolution of macroscopic depositional environments controls the abundance/bio-availability of buried organic matter and thus results in the formation of high-ammonium groundwater through mineralization, whereas the molecular composition of natural organic matter and its degradation pathway at the microscale play a major role in controlling the transport and enrichment of ammonium in groundwater. The direction of future research on high ammonium groundwater that should be deepened and expanded was proposed, mainly including the combination of macro-model and micro-mechanism, the control of the organic carbon age, and the influence of high ammonium groundwater discharge on the nutrient status of surface water.